Acute effects of blood flow restriction with whole-body vibration on sprint, muscle activation and metabolic accumulation in male sprinters - Zhang, Junjie; Zhou, Ruihang; Zhao, Ningning; Li, Yamei; Liu, Haiyuan; Zhang, Wanxia; Guo, Wenxia (Frontiers in Physiology, 2023)
Purpose: The aim of this study was to explore the acute effects of Blood Flow Restriction Training (BFRT), Whole-Body Vibration (WBV), and BFRT + WBV on the 20 m sprint, muscle activation, and metabolic accumulation in male sprinters. Method: Sixteen male sprinters randomly performed BFRT, WBV, or BFRT + WBV interventions with 72 h intervals. Electromyography (EMG) signals were collected before and during interventions. Fingertip blood was taken before, immediately after, and 15 min after the intervention. 20 m sprint was performed before and 3 min after the intervention. Results: 1) 0–10m and 0–20 m sprint performance were significantly improved after WBV and BFRT + WBV interventions (p < 0.05), 0–20 m sprint performance was significantly improved after all three interventions (p < 0.05), 2) After BFRT + WBV intervention, the EMG amplitude of the vastus lateralis and soleus were significantly improved. Greater increases in EMG activity of the tibialis anterior muscle (p < 0.05)and blood lactate (p < 0.05)were observed following BFRT intervention compared to BFRT + WBV intervention. Conclusion: For sprint performance, BFRT and WBV had similar post-activation enhancement effects to BFRT + WBV, and the metabolic accumulation immediately following the BFRT were higher than that following BFRT + WBV in male sprinters.